A Citizen Compliance Evaluation on Traffic Laws - ไชยชุมพล ภานุพงศ์ (Journal of Graduate MCU KhonKaen Campus, 2014)
The study is the Evaluation of the levels of Agreement to follow the road traffics. The objectives of the study is 1) to evaluate the levels of the agreement of people who followed the road traffics 2) to study the factors that effect people’s agreement to follow the road traffics. The researcher used the group of people who used the road transportation in Khon Kaen Municipality and the samples were 300 Khon Kaen people. The tools for collecting research data was questionnaires and the researcher used statistic information analysis to obtain the data result. They were 1) the mean and standard deviation 2) the relation of Pearson Product Moment Correlation 3) the creation of equation with the Multiple Regression Analysis. The Research Result : 1) The level of agreement to follow the road traffics in Khon Kaen Municipality was “average”. 2) Four factors were related positively. All variables showed the statistic significance at the level of 0.01 by ordering the relations from being much to less i.e. the first factor was the Efficient Law Enforcement and it got the correlation coefficient of .664 . The second factor was the use of media which showed the correlation coefficient at .656 . The correlation coefficient of Khon Kaen people’s preparedness for using roads was .656 while the trust on the police as being the law enforcement person was .505. 3) The researcher could predict the best factors that affected the agreement to follow the road traffics composed of the efficient law enforcement, the trust on the police, the preparedness on using roads and the media. And these factors could predict of the levels of the agreement to follow the road traffics law as the percentage were 68.90%